Diastolic Mitral Regurgitation in 2:1 Atrioventricular Block: Insight of the Diastolic Pressure. Issue 2 (8th November 2012) - Kocabay, Gonenc; Peluso, Diletta; Muraru, Denisa; Iliceto, Sabino; Badano, Luigi P.
Mini‐Abstract We present a 74‐year‐old man with a history of hypertension presented to the emergency room with shortness of breath and dizziness. A resting electrocardiogram showed 2:1 atrioventricular block with a wide QRS duration and a rhythm of 35 beats/min. Transthoracic echocardiography was performed and color flow Doppler, color M‐mode, and continuous‐wave Doppler recordings of the transmitral flow revealed retrograde flow into the left atrium after the blocked P‐wave, which indicate holodiastolic mitral regurgitation.